PENATAAN KEMITRAAN DAN KELEMBAGAAN DESA WISATA TISTA, KECAMATAN KERAMBITAN KABUPATEN TABANAN - Suardana. I.W; N M. Ariani (Buletin Udayana Mengabdi, 2011)
Tista village, representing one of the traditional villages of Tabanan Regency owns a unique social aspect, potency and culture so that many tourists pay it a visit. From the result of the discussion with elite figures, travel agencies and government which are competent in terms of supporting tourism village, Tista village has developed the band of tracking. This activity have succeeded in making package tour and also formed institute of tourism village to control tourism activity. The package tour sells what is called ”tourism village” consisting of a package passing enjoyably the ancient commission, tracking, and traditional countryside. In exploiting the tourism attraction, it must keep remaining to pay attention to the value of holy attraction, so that holy cultural value keeps improving our awareness.